ENSEÑANZA INTERDISCIPLINARIA DE LAS CIENCIAS. MATICES PARA EL AULA: REVIEW OF A JOINT BOOK OF MULTIFACETED INTEREST - Vaira, Stella Maris; Walz, María Florencia; Fabro, Ana Patricia (Revista Binacional Brasil-Argentina: Dialogue between the sciences, 2023)
In this review, the reasons, arguments and purposes that led to the publication of the book “Enseñanza interdisciplinaria de las Ciencias. Matices para el aula” published under the publishing label “ediciones UNL”; aimed at educators of different levels, interested in knowing exemplary proposals on how to approach a subject through an interdisciplinary didactic methodology for the teaching of experimental, health and mathematical sciences. The text is complemented by a brief summary of the contents of each chapter of the book.